Isolated visual symptoms at onset in sporadic Creutzfeldt-Jakob disease: the clinical phenotype of the "Heidenhain variant". Issue 10 (16th September 2005) - Cooper, S A; Murray, K L; Heath, C A; Will, R G; Knight, R S G
Abstract : Background: The Heidenhain variant of sporadic Creutzfeldt-Jakob disease (sCJD) is commonly understood to represent cases with early, prominent visual complaints. The term is clarified to represent those who present with isolated visual symptoms. This group may pose diagnostic difficulties and often present to ophthalmologists where they may undergo needless invasive procedures. Method: A retrospective review of 594 pathologically proved sCJD cases referred to the UK National CJD Surveillance Unit over a 15 year period to identify Heidenhain cases. Results: 22 cases had isolated visual symptoms at onset with a mean illness duration of 4 months. The mean age at disease onset was 67 years. Most displayed myoclonus, pyramidal signs, and a delay in the onset of dementia for some weeks. 17 (77%) were referred initially to ophthalmology. Two underwent cataract extraction before diagnosis. All tested cases were homozygous for methionine at codon 129 of the prion protein gene. Conclusions: This rare, but clinically distinct, group of patients with sCJD may cause diagnostic difficulties. Because ocular intervention carries with it the risk of onward transmission awareness of this condition among ophthalmologists is important.